Signal and Noise in the Atlantic Meridional Overturning Circulation at 26°N - Gerard D. McCarthy; Guillaume Hug; David Smeed; Kirsty J. Morris; Ben Moat (Geophysical Research Letters)
Abstract The Atlantic meridional overturning circulation (AMOC) plays a crucial role in redistributing heat within the climate system. The RAPID mooring array has observed an AMOC weakening of 1.0 [0.4–1.6] Sv per decade from 2004 to 2023, consistent with climate model projections and not consistent with a collapse in the mid‐21st century. Here, we analyze the AMOC change within a signal‐to‐noise framework. We find a strong signal in Lower North Atlantic Deep Water (LNADW) and thermocline transports. By removing the influence of Ekman transport on AMOC and LNADW estimates, we reduce noise by 30% and 22%, respectively. Moreover, we demonstrate that a simple model of LNADW yields a comparable signal‐to‐noise ratio to the full AMOC estimate. Ultimately, we conclude that current AMOC trends are unlikely to reach “unfamiliar” (signal‐to‐noise ratio > 2) or “unknown” (signal‐to‐noise ratio > 3) thresholds until the 2040s and 2060s, respectively.